Analisis Bauran Pemasaran Pada UMKM Kuliner - Sir Kalifatullah Ermaya (Coopetition : Jurnal Ilmiah Manajemen, 2022)
The existence of culinary SMEs as the center of economic activity for most Indonesian people has begun to be displaced by the modern market. Therefore, improving service quality is important in increasing consumer loyalty in order to maintain it. Researchers conducted research with qualitative methods and used descriptive statistics to determine the 7P's marketing mix at "Gudeg Wijilan Hj Rini". The sampling technique used is random sampling with the number of respondents 30 people. As for the number of indicators, there are twenty-five that fit into the seven dimensions. In conveying messages about their products to consumers, all dimensions of the 7P marketing mix variable in "Gudeg Wijilan Hj Rini" fall into the high category. The dimension with the best score is promotion with a score of 4.93. Meanwhile, the dimension with the lowest score is process with a score of 4.58. The best indicator is "promotion through various media" with a score of 5.00. While the lowest indicator is "fast ordering process" with a score of 4.37. This shows that "Gudeg Wijilan Hj Rini" has done the 7P marketing mix well. SMEs, culinary, marketing mix, marketing mix